2016
DOI: 10.1097/mao.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants in Adults

Abstract: Older age at testing was associated with poorer recognition of words in difficult sentences, suggesting that cognitive aging may negatively impact CI outcomes. Further studies are needed to examine how a long duration of auditory deprivation affects CI outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 42 publications
1
51
0
2
Order By: Relevance
“…While previous studies have shown mixed results on whether aging and age-related temporal processing deficits affect speech understanding with a CI, there is mounting evidence that older CI listeners perform worse than their younger peers, particularly when duration of deafness is accounted for in the study (Beyea et al 2016; Sladen and Zappler 2015). Many studies in this area use sentence recognition as a metric for CI performance.…”
Section: Discussionmentioning
confidence: 90%
“…While previous studies have shown mixed results on whether aging and age-related temporal processing deficits affect speech understanding with a CI, there is mounting evidence that older CI listeners perform worse than their younger peers, particularly when duration of deafness is accounted for in the study (Beyea et al 2016; Sladen and Zappler 2015). Many studies in this area use sentence recognition as a metric for CI performance.…”
Section: Discussionmentioning
confidence: 90%
“…Younger subjects performed better with monosyllabic words at baseline and maintained this advantage at the 3-and 6-month testing intervals over the older age group as expected. Other authors have noted a relationship between a younger age and better postoperative performance [4,18,[40][41][42]. Holden et al [18] even found that once scalar location had been removed as a variable, age was the only factor that still correlated significantly with outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Low uptake of CI seemingly conflicts with extensive evidence showing that CI improves quality of life (Crowson et al 2017) and improve outcomes in multiple domains when compared to hearing aids, including psychosocial health, functional health and social inclusion (Francis et al 2002;Cohen et al 2004;Bosdriesz et al 2017), while being cost effective (Bond et al 2009). Delaying implantation has been shown to be disadvantageous; evidence suggests a correlation between increasing duration of hearing loss prior to implantation (Blamey et al 2013), as well as links between increasing age at time of implantation and poorer speech recognition scores (Blamey et al 2013;Beyea et al 2016;Hiel et al 2016).…”
Section: Introductionmentioning
confidence: 99%